Tuning Charge Carrier Types, Superior Mobility and Absorption in Lead-free Perovskite CH3NH3GeI3: Theoretical Study. (1st September 2017) - Zhao, Yu-Qing; Liu, Biao; Yu, Zhuo-Liang; Cao, Dan; Cai, Meng-Qiu
Abstract: The toxicity and instability of CH3 NH3 PbI3 limits its widespread application. Lead-free perovskite CH3 NH3 GeI3 as alternative materials has attracted increasing attention for photovoltaic application. In this paper, we present a detailed theoretical investigation of electronic structure of CH3 NH3 GeI3 to predict its transport property and optical performance with meta-GGA functional. The carrier mobility are mainly high electron-dominated and the system is intrinsic or weak p-type semiconductor, offering direct band gap, tunable from 1.35 eV to 2.5 eV under different strain. The applied compressive strain can highly drive carrier mobility and optical absorption. While applying up to 4% strain, electron-hole carrier mobility achieves 3.624 × 10 3  cm 2 V −1 S −1 and 1.633 × 10 3  cm 2 V −1 S −1 respectively and absorption coefficients attain the high value in full visible spectrum, much superior to those of traditional CH3 NH3 PbI3 and Si profile. In addition, we exhibited new approach to tune charge carrier types by applying dilated or compressive strains to induce intrinsic charge of CH3 NH3 GeI3 to turn into p type or n type semiconductor. The energy band engineering by applying strain makes halide CH3 NH3 GeI3 to gain suitable band gap, achieve high carrier mobility and absorption coefficients to become promising material for photovoltaic application.